XIMIYA SABAǴÍNDA INTEGRACIYALASQAN OQÍTÍW - Jarekeyeva, D.; Abdisattarova, E.; Sultanov, M. (ILIM hám JÁMIYET, 2024)
This article provides a brief definition of the concept “integration”. The integration of chemistry with biology, geography, everyday life, the environment, medicine, history and english is presented with examples to enhance the teaching of chemistry in school.